Hourly Wages in Crowdworking: A Meta-Analysis - Lars Hornuf; Daniel Vrankar (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the past decade, crowdworking on online labor market platforms has become the main source of income for a growing number of people worldwide. This development has led to increasing political and scientific interest in the wages that people can earn on such platforms. In this article, we extend the literature based on a single platform, region, or category of crowdworking by conducting a meta-analysis of the prevalent hourly wages. After a systematic and rigorous literature search, we consider 20 primary empirical studies, including 104 wages and 76,282 data points from 22 platforms, eight different countries, and a time span of 12 years. We find that, on average, microwork results in an hourly wage of less than 6. This wage is significantly lower than the mean wage of online freelancers, which is roughly three times higher. We find that hourly wages accounting for unpaid work, such as searching for tasks and communicating with requesters, tend to be significantly lower than wages not considering unpaid work. Legislators and researchers evaluating wages in crowdworking should be aware of this bias when assessing hourly wages, given that the majority of the literature does not account for the effect of unpaid work time on crowdworking wages. To foster the comparability of different research results, we suggest that scholars consider a wage malus to account for unpaid work. Finally, we find that hourly wages collected through surveys tend to be lower than wages collected via browser plugins or other technical data collection methods.
Keywords: J30; J81; M50; O33; 330; crowdworking; crowdsourcing; meta-analysis; hourly wage; remuneration; Gig-economy